Innovation in Design and Development of Corruption Detection Tool Applications (AKSI) - Aldi Adi Pratama; Kiki Yulianto (International Journal of Science, Engineering, and Information Technology, 2022)
The AKSI (Alat Pendeteksi Tindak Pidana Korupsi) application is the latest prototype innovation tool in community service activities for the independent campus program, with the topic of artificial intelligence (AI). This innovation is said to be important in service, because it is a form of service to the community for a community organization for the supervisory function. The community has the right to oversee the running of community institutions or company organizations, based on the scope of rights and placements when working. In addition, this tool also emphasizes proof of presumptions against certain parties, who are said to have committed acts of corruption. In the implementation of this independent campus program, using the method of observation and descriptive approach. The observation method is very suitable for applications that are limited to prototypes. While the descriptive analysis method is a method or way of working in a problem solving by describing, describing and explaining and analyzing the condition of a problem object from the author's point of view based on the results of a literature review that supports the study of literature. However, the implementation of this service is still said to be a design, and is still in the orientation stage based on the systematic use of artificial intelligence when applied to social case studies in the community.